Understanding the entrepreneurial resilience of indigenous women entrepreneurs as a dynamic process. The case of Quechuas in Bolivia - Padilla-Meléndez, Antonio; Ciruela-Lorenzo, Antonio Manuel; Del-Águila-Obra, Ana Rosa; Plaza-Angulo, Juan José (Taylor & Francis, 2022)
Little literature exists regarding the study of entrepreneurial resilience of indigenous women entrepreneurs (IWEs) in environments challenged with isolation, marginalization, or poverty. New insights that explain the role of resilience in the creation, survival, and development of entrepre- neurial activities by indigenous people are needed. In this research, we defined, in the context of IWEs, the individual traits embedded in entre- preneurial resilience. Then, we applied a qualitative approach to analyse the cases of 32 IWEs, these being current entrepreneurs located in street or organized markets in Cochabamba (Bolivia). Interviews and self- identified critical life incidents were used to illustrate how these IWEs developed their entrepreneurial activities and how resilience influenced the emergence and improvement of those activities over time. This work contributes to the entrepreneurship literature: first, by showing how IWEs’ individual entrepreneurial resilience traits help to explain the develop- ment of entrepreneurial activities, as a way of survival and personal improvement and, second, by proposing the dynamic entrepreneurial resilience spiral as a process of increasing individual resilience and build- ing community resilience, where the IWEs empowerment plays a key role overcoming environmental circumstances, with education and training developing a leverage effect.
Keywords: Mujeres indígenas; Emprendedoras; Entrepreneurial resilience; Individual traits; Indigenous women entrepreneurs; Quechua; Bolivia